Measuring The Impact Of Intrinsic And Extrinsic Factors On Job Satisfaction Of Teachers During Covid-19 - RASTOGI, MEGHA; DHINGRA, DR. VAISHALI (The journal of contemporary issues in business and government, 2021)
Objective: The main objective of the research is to determine the influence of intrinsic and extrinsic factors on job satisfaction of teachers during COVID-19. Method: It is descriptive research for which data was collected between August 2020 and October 2020 through Minnesota Satisfaction Questionnaire. Due to preventive measures of Corona, data was collected through mail. Questionnaire was mailed to 160 teachers working in 7 different colleges of Northwestern region of India. The response rate was 63%. The data was analyzed by descriptive statistics (mean, standard deviation), T-test and One-way ANOVA. Result: The outcome of the research work shows no significant relation exist between demographic variables (gender, marital status, number of children, educational qualification and working duration) and job satisfaction of teachers. Conclusion: Result of the study indicate that whether one is male or female, married or unmarried, with children or without children, with different education qualification and working duration, the intrinsic and extrinsic factors influence their job satisfaction.